2018
DOI: 10.1016/j.pmedr.2018.05.013
|View full text |Cite
|
Sign up to set email alerts
|

A national survey of primary care physicians: Perceptions and practices of low-dose CT lung cancer screening

Abstract: Soon after the National Lung Screening Trial, organizations began to endorse low-dose computed tomography (LCDT) screening for lung cancer in high-risk patients. Concerns about the risks versus benefits of screening, as well as the logistics of identifying and referring eligible patients, remained among physicians. This study aimed to examine primary care physicians' knowledge, attitudes, referral practices, and associated barriers regarding LDCT screening. We administered a national survey of primary care phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 34 publications
5
50
0
1
Order By: Relevance
“…8,9 An increased rate of LCS referral since 2013 is consistent with a recent national study in which 36% of providers reported ordering 1 to 5 tests in the past year. 24 However, ,1% of gynecologists and only 39% of hematology/oncology providers reported performing LDCT screening in the past year in our study. Having a patient population that is ineligible for screening (ie, younger nonsmokers) or assuming that another provider is addressing cancer screening may explain lower knowledge or rates of screening among these providers.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…8,9 An increased rate of LCS referral since 2013 is consistent with a recent national study in which 36% of providers reported ordering 1 to 5 tests in the past year. 24 However, ,1% of gynecologists and only 39% of hematology/oncology providers reported performing LDCT screening in the past year in our study. Having a patient population that is ineligible for screening (ie, younger nonsmokers) or assuming that another provider is addressing cancer screening may explain lower knowledge or rates of screening among these providers.…”
Section: Discussionmentioning
confidence: 54%
“…Consistent with prior studies, many providers still report ordering screening chest radiographs, which is not a recommended screening test. 4,11,13,19,21,24 It is not surprising that there were more providers with low LCS knowledge who reported ordering screening chest radiographs. However, to our knowledge, this is the first study showing this relationship, and this finding further strengthens the relationship between guideline knowledge and LCS.…”
Section: Discussionmentioning
confidence: 99%
“…However, perceived time constraints are the most frequently cited barrier to proposed change in clinical settings. Findings from a recently completed national survey of 810 PCPs (430 medical doctors and 380 nurse practitioners in the U.S.) indicated that only 30% and 37%, respectively, would be likely to engage in an SDM discussion with a patient if the time commitment was greater than 8 minutes . In this sense, implementing SDM may be no different from implementing any other practice improvement .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, 75% of PCPs reported in a national survey that the benefits of screening outweigh the harms but only 5% had actually billed CMS for a shared decision-making visit. 23 They reported many procedural barriers to shared decisionmaking such as competing patient priorities and lack of time: 67% indicated they would not engage in shared decision-making if it took > 8 min.…”
Section: Circumstantial Evidence Of Benefit and Harms From Requiring mentioning
confidence: 99%